Charge transport control via polymer polymorph modulation in ternary organic photovoltaic composites - Kan, Zhipeng; Colella, Letizia; Canesi, Eleonora V.; Vorobiev, Alexei; Skrypnychuk, Vasyl; Terraneo, Giancarlo; Barbero, David R.; Bertarelli, Chiara; MacKenzie, Roderick C. I.; Keivanidis, Panagiotis E. (My University, 2015)
The control on the charge transport properties of ternary organic photovoltaic P3HT:PCBM:QBT devices is enabled by modulating the distribution of P3HT polymorphs in the device photoactive layers. Negligible amounts of QBT induce striking modifications in the P3HT lamellar stacking direction, forming both densely packed and non-densely packed P3HT chains. The former reduce the charge carrier recombination rate, enabling an increased fill factor and short-circuit device photocurrent.
Keywords: Charge carrier recombination; Fill factor; Is-enabled; Organic photovoltaics; Photoactive layers; Transport control